Public relations as a tool of communication between health care organizations and patients - Wroński, Konrad; Okraszewski, Jerzy; Bocian, Roman (Contemporary Oncology/Współczesna Onkologia, 2008)
In a modern economy each organization working under circumstances of global competition must build good relationships between their customers and suppliers, as well as future customers and future suppliers. At the end of the twentieth century and early twenty-first century, rapid development of modern communication technologies has been observed worldwide. One of the most effective means of communication between organizations and the environment is public relations. Health care units as organizations operating in the free market must also use public relations to maintain direct contact with their patients. Those hospitals which fail to recognize the importance of communication with society will disappear from the medical services market sooner or later.